Time Profile of nNOS Expression in the Spinal Dorsal Horn After L₅ Spinal Root Transection in Rats - Bahari, Z.; Manaheji, H.; Dargahi, L.; Daniali, S.; Norozian, M.; Meftahi, G.H.; Sadeghi, M. (Нейрофизиология, 2015)
Using immunohistochemical analysis, we investigated the time profile of neuronal nitric oxide synthase (nNOS) expression in the lumbar spinal cord up to day 28 after transection of the L₅ spinal root. On day 14 after injury, we also evaluated the effect of intrathecal application of 7-nitroindazole (7-NI), a selective nNOS inhibitor (8.15 µg in 5 µl), on thermal hyperalgesia. Our results indicated that nerve transection increased the intensity of nNOSimmunoreactivity in superficial and deep laminae of the dorsal horn within a late stage (days 7 to 28) of the neuropathy model used. Furthermore, 7-NI attenuated nerve injury-evoked thermal hypersensitivity on day 14 but did not reduce it between days 2 and 5 after transection. These data suggest that nNOS overexpression is more involved in the development than in the initiation of thermal hyperalgesia in L₅ -transected rats.